2012
DOI: 10.14569/ijacsa.2012.030130
|View full text |Cite
|
Sign up to set email alerts
|

Transform Domain Fingerprint Identification Based on DTCWT

Abstract: Abstract-The physiological biometric characteristics are better compared to behavioral biometric identification of human beings to identify a person. In this paper, we propose Transform Domain Fingerprint Identification Based on DTCWT. The original Fingerprint is cropped and resized to suitable dimension to apply DTCWT. The DTCWT is applied on Fingerprint to generate coefficient which form features. The performance analysis is discussed with different levels of DTCWT and also with different sizes of Fingerprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The percentage values of TSR and EER of proposed method is compared with existing methods presented by Chaven et al [9], George et al [17], Jadhav and Ajmera [21] and Roja and Sawarkar [35]. It is observed that the value of TSR is high in the case of proposed method compared to existing methods (Table 6).…”
Section: Performance Comparison Of Proposed Technique With Existing Techniquesmentioning
confidence: 87%
“…The percentage values of TSR and EER of proposed method is compared with existing methods presented by Chaven et al [9], George et al [17], Jadhav and Ajmera [21] and Roja and Sawarkar [35]. It is observed that the value of TSR is high in the case of proposed method compared to existing methods (Table 6).…”
Section: Performance Comparison Of Proposed Technique With Existing Techniquesmentioning
confidence: 87%
“…Hardwarerelated systems utilize more equipment and readers to capture biometric measures other than fingerprints to detect liveness. Such systems used additional equipment to record biological signals such as fingertip temperature, electric resistance, blood pressure, odor, or heartbeat [5][6][7]. Nixon and Rowe proposed a multispectral reader in which several light wavelengths and multiple polarizations provide extra data not available from a traditional system.…”
Section: Introductionmentioning
confidence: 99%